Covalently bonded nanosilver-hydroxyethyl cellulose/polyacrylic acid/sorbitol hybrid matrix: thermal, morphological and antibacterial properties - BİRTANE, HATİCE; KAHRAMAN, MEMET VEZİR (SPRINGER, 2022)
In this study, an antibacterial, biodegradable, biocompatible, and environmentally friendly coating was prepared with an easy technique. Accordingly, Ag nanoparticles were synthesized to provide antibacterial properties to the coating, and its surface was modified with (3-Glycidyloxypropyl)trimethoxysilane (GPTMS) in order not to clump in the coating, to ensure homogeneous distribution on the surface, and to covalently bond to the coating. While preparing the coating formulation, polyacrylic acid (PAA), which are natural polymers, and hydroxyethyl cellulose (HEC), a derivative of cellulose, were preferred to reduce the consumption of petroleum derivatives. Then, sorbitol was used as a plasticizer. Synthesized Ag nanoparticles were included in the coating formulation containing PAA/HEC and sorbitol and thermally crosslinked at a high temperature. The size of Ag nanoparticles was analyzed by DLS while chemical composition after modification was analyzed by FTIR. Then, the chemical structure, thermal properties, surface properties, and antibacterial properties of the environmentally-friendly film were examined. It was observed that Ag nanoparticles, the surface of which were modified with GPTMS containing silicon groups, increased the thermal stability of the film, and the presence of Si and Ag on the surface was detected in SEM-EDAX measurements, and this showed that the aimed coating was obtained. It was observed that silver nanoparticles, of which their surface was modified, incorporated into the coating obtained from PAA and HEC, which are known to have no antibacterial properties, showed antibacterial activity against E. coli and S. aureus. The zone of inhibition was measured as 11 mm for both E. coli and S. aureus.
Keywords: Hydroxyethylcellulose; Environmentally-friendly coating; Antibacterial coating; Ag nanoparticles; Surface modification; SILVER NANOPARTICLES; CELLULOSE; COMPOSITE; HYDROGEL; EFFICACY; FILM